PENGARUH PELATIHAN DAN DISIPLIN TERHADAP EFEKTIFITAS KERJA PESONIL PADA KANTOR SAT LANTAS POLRES LAHAT - Rusilawati Kasisariah, Tri; Garaika, Garaika; Sarwo Sari, Sri; Hayani, Hayani (AKTUAL, 2025)
Work effectiveness is the overall implementation of physical and spiritual activities carried out by personnel to achieve a specific goal. Efforts to increase effectiveness, raise awareness of productivity, efficiency, entrepreneurship, and work ethic are implemented through various activities such as improving discipline and training. The purpose of this study was to determine and analyze the effect of training on the work effectiveness of personnel at the Lahat Police Traffic Unit Office, to determine and analyze the effect of discipline on the work effectiveness of personnel at the Lahat Police Traffic Unit Office, and to determine and analyze the effect of training and discipline on the work effectiveness of personnel at the Lahat Police Traffic Unit Office. Primary data in this study were obtained by distributing questionnaires to 67 personnel at the Lahat Police Traffic Unit Office. The data analysis technique used was SPSS version 23.0, using data testing and statistical testing. The results of the data analysis of the studied variables, namely Training and Discipline, indicate an influence on the work effectiveness of personnel at the Lahat Police Traffic Unit Office, both simultaneously and partially.